Denture base composite material and preparation process thereof
The denture base composite material prepared by modifying the suspension polymerization method of tourmaline and functional polymer monomers solves the problem of insufficient toughness and cleanliness of existing materials, achieves higher mechanical strength and antibacterial properties, and improves the denture's Use effect.
Patent Information
- Application Number
- CN202411522484.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing polymethyl methacrylate-based tray materials have poor toughness, poor mechanical properties, easy to break during bite, and difficult to clean, affecting the use effect of dentures.
Modified tourmaline and functional polymeric monomers are used as raw materials, and in-situ polymerization is carried out on the surface of calcium carbide gas by suspended polymerization to prepare denture base composite materials with enhanced mechanical strength and antibacterial properties.
It improves the mechanical strength and antibacterial properties of the composite material, reduces the adhesion of food residues, improves the oral microbial environment, and extends the service life of the denture.
Smart Images

Figure CN119390914A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of materials, and in particular to a denture base composite material and a preparation process thereof. Background Art
[0002] In the broad field of stomatology, dentures (false teeth) are an important means to restore the function of missing teeth, improve facial morphology and enhance the quality of life of patients. The selection and development of their manufacturing materials have always been one of the key factors in promoting the advancement of oral restoration technology. As the supporting structure of the denture, the denture base not only carries the important mission of restoring physiological functions such as chewing and pronunciation, but also directly affects the comfort, aesthetics and durability of the denture. Therefore, it is necessary to have good biocompatibility, mechanical strength, stability, processing performance and certain aesthetics. According to the different properties of the materials, denture base materials can be roughly divided into several categories, including traditional plastic base materials, metal base materials, ceramic base materials and new composite materials. Among them, the plastic base material is mainly made of polymethyl methacrylate as the raw material. Its advantages are good processing performance, easy shaping, grinding and polishing, and relatively low cost, which is suitable for the economic affordability of most patients. In addition, the PMMA base material has a stable color and is not easy to change color. It can meet the basic aesthetic needs, so it has a wide range of applications.
[0003] However, polymethyl methacrylate itself has poor toughness and poor mechanical properties. It often breaks when biting, which in turn causes the base to break, resulting in dysbiosis and even denture stomatitis. It has obvious defects in practical applications. In addition, there are often food residues in the mouth. These food residues will adhere to the gaps between the teeth and are difficult to clean. Therefore, the preparation of polymethyl methacrylate composite materials that are easy to clean and have excellent mechanical properties is of great significance to the further development of the denture industry. Summary of the invention
[0004] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a denture base composite material and a preparation process thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A preparation process of a denture base composite material, wherein the composite material is made of the following raw materials in parts by weight:
[0007]
[0008] The preparation process comprises the following steps:
[0009] The first step is to weigh each raw material according to the weight and set aside;
[0010] The second step is to add the modified tourmaline into purified water, and after ultrasonic dispersion, add the activator, ultrasonicate at an ultrasonic frequency of 80-100kHz for 10-30 minutes, turn on the heating, control the temperature to 70-75°C, add methyl methacrylate, functional polymerization monomer and initiator under stirring conditions, and after the addition, raise the temperature to 78-82°C, keep warm for 8-16 hours, stop heating, wait for the material to cool, filter and separate the product, and then obtain a composite material.
[0011] As a further solution of the present invention, the preparation method of the functional polymer monomer is as follows:
[0012] Step S1, adding curcumin and anhydrous toluene into a reactor filled with nitrogen, and after the addition, stirring is started until the mixture is uniformly mixed, which is recorded as the first mixed solution, and adding allyl dichloro(methyl)silane into the anhydrous toluene, mechanically stirring and mixing the mixture uniformly, which is recorded as the second mixed solution;
[0013] Step S2, at a stirring rate of 1000-1500 r / min, add the second mixed liquid to the first mixed liquid to form a reaction liquid, add the acidifying agent to the reaction liquid, and then gradually increase the temperature to 60-65°C. After stirring for 8-12 hours under this temperature condition, evaporate the solvent, cool and discharge the material, and the functional polymer monomer can be obtained.
[0014] As a further embodiment of the present invention, in step S2, the molar ratio of curcumin to allyldichloro(methyl)silane in the reaction solution is 1-1.2:1.
[0015] As a further embodiment of the present invention, in step S2, the acidifying agent is pyridine or triethylamine.
[0016] In the above technical scheme, curcumin and allyldichloro(methyl)silane are used as reactants. Under the action of an acidifying agent, the active hydroxyl substituents and silicon-chloride groups in each other's structures can be continuously substituted to form a block-type macromolecular substance connected by silicon-oxygen bonds. The structure of the macromolecular substance contains a large number of unsaturated alkenyl substituents, which can participate in subsequent free radical copolymerization reactions.
[0017] As a further embodiment of the present invention, the preparation method of the modified tourmaline is as follows:
[0018] Tourmaline is mixed with 1,4-dioxane, and ultrasonically dispersed to form a uniform dispersion. A surface functionalization modification agent is then added to the dispersion. After the addition, nitrogen is introduced, the air is exhausted, and the heating is turned on to raise the temperature to 40-50°C. After heat preservation for 3-6 hours, the material is cooled and discharged, and the solid material is centrifuged out. After washing and vacuum drying, the modified tourmaline can be obtained.
[0019] As a further embodiment of the present invention, the mass ratio of the tourmaline to the surface functionalization modification agent is 1:2-3.5.
[0020] As a further embodiment of the present invention, the surface functionalization modification agent is diallylcarbamoyl chloride.
[0021] In the above technical scheme, the tourmaline surface contains active hydroxyl groups. By using diallylcarbamoyl chloride as a surface functionalization modification agent, the tourmaline is surface olefinic functionalized to obtain a tourmaline containing a large number of unsaturated olefinic functional groups on the surface, i.e., modified tourmaline.
[0022] As a further embodiment of the present invention, the activator is sodium dodecylbenzene sulfonate or sodium dodecyl sulfate.
[0023] As a further embodiment of the present invention, the initiator is azobisisobutyronitrile or azobisisoheptanenitrile.
[0024] A denture base composite material is prepared by adopting the above preparation process.
[0025] Beneficial effects of the present invention:
[0026] The present invention adopts suspension polymerization method to make methyl methacrylate and functional polymerization monomers polymerize in situ on the surface of calcium carbide gas to prepare denture base composite material. First, tourmaline exists in the composite material in the form of chemical bonds. On the one hand, it can play a role in transmitting and dispersing stress loads and enhancing the mechanical strength of the composite material. On the other hand, chemical bonding is conducive to the uniform dispersion of tourmaline. The characteristic of tourmaline that can release negative ions is used to regulate the balance of oral function.
[0027] The functional polymer monomer structure contains a large number of silicon-oxygen bonds, which are highly hydrophobic and can give the composite material a hydrophobic and oleophobic effect, reducing the adhesion of food residues on the tooth surface. In addition, the large amount of curcumin contained in its structure has a broad-spectrum antibacterial effect, which can eliminate oral bacteria and improve the oral microbial environment.
[0028] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0030] Figure 1This is the infrared analysis test diagram of functional polymerization monomer. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Preparation Example 1
[0033] Preparation of functional polymer monomers:
[0034] Step S1, add 1.2g of curcumin and 100mL of anhydrous toluene to a reactor filled with nitrogen, start stirring after adding, wait until mixed evenly, record as the first mixed solution, add 0.45g of allyldichloro(methyl)silane to 100mL of anhydrous toluene, stir mechanically to mix evenly, record as the second mixed solution;
[0035] Step S2, at a stirring rate of 1500r / min, add the second mixed liquid to the first mixed liquid to form a reaction liquid, add 0.1g of pyridine to the reaction liquid, and then gradually increase the temperature to 65°C. After stirring for 9 hours under this temperature condition, evaporate the solvent, cool and discharge the material, and the functional polymerization monomer can be obtained.
[0036] The functional polymer monomer was made into potassium bromide tablets and subjected to infrared analysis test. The results are shown in Figure 1 , of which 3211cm -1 The absorption peak at 3092 cm is the characteristic absorption peak of hydroxyl group. -1 and 3067cm -1 The absorption peak at 3008 cm is the carbon-hydrogen absorption peak on the benzene ring skeleton of curcumin. -1 The absorption peak at 1000-1100 cm is the characteristic absorption peak of carbon-hydrogen on the unsaturated carbon-carbon double bond. -1 The absorption peaks appearing at are the characteristic absorption peaks of the overlapping ether bonds and silicon-oxygen bonds.
[0037] Preparation Example 2
[0038] Preparation of modified tourmaline:
[0039] Mix 2.4 g of tourmaline with 1,4-dioxane, and disperse them by ultrasonic until a uniform dispersion is formed. Then, add 6 g of diallylcarbamoyl chloride to the dispersion. After the addition, introduce nitrogen, exhaust the air, turn on the heating, raise the temperature to 50°C, keep the temperature for 4 hours, cool the material, centrifuge the solid material, and obtain the modified tourmaline after washing and vacuum drying.
[0040] Example 1
[0041] A denture base composite material is made of the following raw materials in parts by weight:
[0042]
[0043] The preparation process of the composite material comprises the following steps:
[0044] The first step is to weigh each raw material according to the weight and set aside;
[0045] The second step is to add the modified tourmaline into purified water, and after ultrasonic dispersion, add sodium dodecylbenzene sulfonate, ultrasonicate at an ultrasonic frequency of 80 kHz for 30 minutes, turn on the heating, control the temperature to 70°C, add methyl methacrylate, functional polymerization monomer and azobisisobutyronitrile under stirring conditions, and after the addition, raise the temperature to 78°C, keep warm for 16 hours, stop heating, wait for the material to cool, filter and separate the product, and then you can get a composite material.
[0046] The preparation method of the functional polymer monomer is shown in Preparation Example 1, and the preparation method of the modified tourmaline is shown in Preparation Example 2, and the same applies to the following.
[0047] Example 2
[0048] A denture base composite material is made of the following raw materials in parts by weight:
[0049]
[0050]
[0051] The preparation process of the composite material comprises the following steps:
[0052] The first step is to weigh each raw material according to the weight and set aside;
[0053] The second step is to add the modified tourmaline into purified water, and after ultrasonic dispersion, add sodium dodecyl sulfate, ultrasonicate at an ultrasonic frequency of 100 kHz for 20 minutes, turn on the heating, control the temperature to 75°C, add methyl methacrylate, functional polymerization monomer and azobisisoheptanenitrile under stirring conditions, and after the addition, raise the temperature to 80°C, keep warm for 12 hours, stop heating, wait for the material to cool, filter and separate the product, and then obtain a composite material.
[0054] Example 3
[0055] A denture base composite material is made of the following raw materials in parts by weight:
[0056]
[0057] The preparation process of the composite material comprises the following steps:
[0058] The first step is to weigh each raw material according to the weight and set aside;
[0059] The second step is to add the modified tourmaline into purified water, and after ultrasonic dispersion, add sodium dodecylbenzene sulfonate, ultrasonicate at an ultrasonic frequency of 100 kHz for 10 minutes, turn on the heating, control the temperature to 75°C, add methyl methacrylate, functional polymerization monomer and azobisisobutyronitrile under stirring conditions, and after the addition, raise the temperature to 82°C, keep warm for 8 hours, stop heating, wait for the material to cool, filter and separate the product, and then obtain a composite material.
[0060] Comparative Example 1
[0061] A denture base composite material is made of the following raw materials in parts by weight:
[0062]
[0063] The preparation process of the composite material comprises the following steps:
[0064] The first step is to weigh each raw material according to the weight and set aside;
[0065] The second step is to add the modified tourmaline into purified water, and after ultrasonic dispersion, add sodium dodecyl sulfate, ultrasonicate at an ultrasonic frequency of 100 kHz for 20 minutes, turn on the heating, control the temperature to 75°C, add methyl methacrylate and azobisisoheptanenitrile under stirring, and after the addition, raise the temperature to 80°C, keep warm for 12 hours, stop heating, wait for the material to cool, filter and separate the product, and obtain a composite material.
[0066] Comparative Example 2
[0067] A denture base composite material is made of the following raw materials in parts by weight:
[0068]
[0069] The preparation process of the composite material comprises the following steps:
[0070] The first step is to weigh each raw material according to the weight and set aside;
[0071] The second step is to add tourmaline into purified water, and after ultrasonic dispersion, sodium dodecyl sulfate is added. After ultrasonication at an ultrasonic frequency of 100 kHz for 20 minutes, heating is turned on and the temperature is controlled to 75°C. Methyl methacrylate, functional polymerization monomer and azobisisoheptanenitrile are added under stirring. After the addition is completed, the temperature is raised to 80°C. After heat preservation for 12 hours, heating is stopped. After the material is cooled, the product is filtered, separated and collected to obtain a composite material.
[0072] Test Case
[0073] The composite materials in the embodiments and comparative examples were made into standard test samples and subjected to comprehensive performance tests. The test results are recorded in Table 1:
[0074] Table 1 - Test results
[0075]
[0076] Note: The test method of tensile strength refers to the standard GB / T 1040-1992;
[0077] The test method for bending strength refers to the standard GB / T 9341-2008;
[0078] The test method for impact strength refers to the standard GB / T 1843-2008;
[0079] The antibacterial rate test method refers to the standard QB / T 2591-2003.
[0080] The water contact angle was tested using a water contact angle meter.
[0081] From the analysis of the test results, it can be concluded that the composite material prepared using modified tourmaline and functional polymer monomers as raw materials has excellent mechanical properties and antibacterial properties, and the water contact angle exceeds 150°, showing super hydrophobicity and easy-to-clean effect.
[0082] After removing the functional polymer monomer, it is obvious that the composite material no longer has a superhydrophobic effect, but due to the presence of tourmaline, it can still exhibit certain antibacterial properties.
[0083] After the modified tourmaline is replaced by tourmaline, due to the interface problems between tourmaline and polymethyl methacrylate, it cannot effectively exert its own reinforcement advantages, resulting in a significant decrease in the mechanical properties of the composite material.
[0084] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
[0085] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A process for preparing a denture base composite material, characterized in that: The composite material is made of the following raw materials in parts by weight: The preparation process comprises the following steps: The first step is to weigh each raw material according to the weight and set aside; The second step is to add the modified tourmaline into purified water, and after ultrasonic dispersion, add the activator, ultrasonicate at an ultrasonic frequency of 80-100kHz for 10-30 minutes, turn on the heating, control the temperature to 70-75°C, add methyl methacrylate, functional polymerization monomer and initiator under stirring conditions, and after the addition, raise the temperature to 78-82°C, keep warm for 8-16 hours, stop heating, wait for the material to cool, filter and separate the product, and then obtain a composite material.
2. The process for preparing a denture base composite material according to claim 1, characterized in that: The preparation method of the functional polymer monomer is as follows: Step S1, adding curcumin and anhydrous toluene into a reactor filled with nitrogen, and after the addition, stirring is started until the mixture is uniformly mixed, which is recorded as the first mixed solution, and adding allyl dichloro(methyl)silane into the anhydrous toluene, mechanically stirring and mixing the mixture uniformly, which is recorded as the second mixed solution; Step S2, at a stirring rate of 1000-1500 r / min, add the second mixed liquid to the first mixed liquid to form a reaction liquid, add the acidifying agent to the reaction liquid, and then gradually increase the temperature to 60-65°C. After stirring for 8-12 hours under this temperature condition, evaporate the solvent, cool and discharge the material, and the functional polymer monomer can be obtained.
3. The process for preparing a denture base composite material according to claim 2, characterized in that: In step S2, the molar ratio of curcumin to allyldichloro(methyl)silane in the reaction solution is 1-1.2:
1.
4. The process for preparing a denture base composite material according to claim 2, characterized in that: In step S2, the acidifying agent is pyridine or triethylamine.
5. The process for preparing a denture base composite material according to claim 1, characterized in that: The preparation method of the modified tourmaline is as follows: Tourmaline is mixed with 1,4-dioxane, and ultrasonically dispersed to form a uniform dispersion. A surface functionalization modification agent is then added to the dispersion. After the addition, nitrogen is introduced, the air is exhausted, and the heating is turned on to raise the temperature to 40-50°C. After heat preservation for 3-6 hours, the material is cooled and discharged, and the solid material is centrifuged out. After washing and vacuum drying, the modified tourmaline can be obtained.
6. The process for preparing a denture base composite material according to claim 5, characterized in that: The mass ratio of the tourmaline to the surface functional modification agent is 1:2-3.
5.
7. The process for preparing a denture base composite material according to claim 5, characterized in that: The surface functionalization modification agent is diallylcarbamoyl chloride.
8. The process for preparing a denture base composite material according to claim 1, characterized in that: The activator is sodium dodecylbenzene sulfonate or sodium dodecyl sulfate.
9. The process for preparing a denture base composite material according to claim 1, characterized in that: The initiator is azobisisobutyronitrile or azobisisoheptanenitrile.
10. A denture base composite material, characterized in that: The method is prepared by the preparation process according to any one of claims 1 to 9.
Citation Information
Patent Citations
Anti-antibacterial complete denture and preparation method thereof
CN110384616A
Long-acting antibacterial material, dental diaphragm and long-acting invisible appliance
CN112998884A
Reinforced toughness type antibacterial denture base and preparation method thereof
CN113181061A
Denture base material and preparation method thereof
CN117426987A
omitted
KR1020050106363A